Internalisasi Nilai-nilai Pendidikan Agama Anak Asuh oleh Asisten Rumah Tangga pada Keluarga Wanita Karir - Alifah Amaliena; Jauharotul Makniyah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2022)
Family has very important role in the children education process. The responsibility o parents in education is the first educator, especially the role of the mother is the most important role. But in reality, currently there are some women who work outside the home and must be willing to leave their children and fully hand over childcare to household assistants for a task they are assigned. In this condition, with all the limitations the housewife replaces the role of her biological mother not only in the aspect of care, but also in education. This study aims to determine how the internalization process of household assistant in internalize religious values in their foster children and what are the supporting and inhibiting factors for internalizing household assistants in instilling religious values in their foster children. The method in this study used qualitative approach with a type of case study. Data sources in this study were interviews, observation and documentation. And the sampling technique using porpusive sampling. Based on the results of this study, the process of internalizing household assistants in internalize the religious education values has a very positive impact children, children can receive religious education and practice it in their daily life.